'His Political Life Story Told in Pictures': The Visual Construction of the Political Persona of Joseph Chamberlain. Issue 1 (2nd January 2022) - van Waarden, Betto
Abstract : This article argues that the increasing use of press images around 1900 contributed to the construction of the political persona of the British Statesman Joseph Chamberlain. These images fused scenes from his public and private life and, paradoxically, the new focus on his private characteristics reinforced his public role. His private life did not replace his public side, nor was the private unrelated to politics as celebrity scholarship suggests, but these projected private characteristics widened the scope of what it meant to be a politician in a mass mediated environment. This argument is made through an analysis of the media context in which Chamberlain matured as a politician and the press images of his public and private life. Particularly the many (re)published images of Chamberlain during the 'media event' of his death in 1914 are used methodologically to trace the evolution of the visual depiction of politics through time.